Democratisation and health after the fall of the Wall (2006)
ABSTRACT: Objectives: The fall of the Wall in 1989 can be seen as a natural experiment in the epidemiological sense to further examine the relation between democracy and health. Design and setting: Ecological study in the 23 post-communist countries, during the last decade of the 20th century, exploring the relations between the level of democratisation and health, taking into account as relevant confounders wealth and the level of inequality. Main results: A significant correlation (p<0.01) was found of the democratic deficit of the countries with the health indicators circa 2000, with values of Pearson’s coefficient of −0.629 for life expectancy, 0.760 for infant mortality, and 0.555 for maternal mortality. These associations remain significant after adjustment by lineal regression for GNP per capita and the Gini coefficient, with R2 values of 0.336 for life expectancy, 0.575 for infant mortality, and 0.529 for maternal mortality. Conclusions: These findings add pieces of evidence to the previously reported cross sectional association between democracy and health.